A kind of graphene oxide / PBO composite fiber and preparation method thereof
By adding small-sized graphene oxide to the preparation of PBO fibers, the tensile strength, modulus and thermal stability of the fibers are improved, and the problems of complex processes and low tensile strength are solved, thus achieving low cost and high performance Industrial production of graphene oxide/PBO composite fibers.
Patent Information
- Application Number
- CN202411293526.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing PBO fibers have complex preparation processes and low tensile strength, which limits their application in high-performance composite materials and is difficult to industrially produce.
The preparation method of small-sized graphene oxide (100nm~6μm) and PBO composite fibers was adopted, and terephthalic acid, 4,6-diaminoisosorcinol hydrochloride, phosphorus pentoxide, polyphosphoric acid and graphite oxide were used. Ethylene is a raw material, and after degassing, prepolymerization and defoaming, graphene oxide/PBO composite fiber is made by polymerization and spinning to improve the inter-chain force and surface polarity of the fiber.
It improves the tensile strength, modulus, thermal stability and compressive strength of PBO fibers, reduces production costs, simplifies the process flow, and is suitable for industrial scale production.
Smart Images

Figure CN118814310B_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a graphene oxide / PBO composite fiber and a preparation method thereof, and specifically relates to a method for engineering the preparation of graphene oxide / PBO composite fibers and the PBO composite fibers prepared by the method, and belongs to the technical field of polymer compound synthesis. Background Art
[0002] PBO fiber, full name Poly-p-phenylene benzobisoxazole fiber, is a high-performance organic synthetic fiber, belonging to aromatic heterocyclic polymers. It is currently the best high-performance organic fiber with the best mechanical properties. Its strength reaches 5.8Gpa, and its tensile modulus reaches 280Gpa, which is the highest among organic fibers and higher than aramid III fiber. It has good heat resistance, and its thermal decomposition temperature reaches 650℃, which is the highest among organic fibers. It can still maintain good mechanical properties at high temperatures, and its use temperature range can reach about 300℃. In addition, it also has excellent acid and alkali corrosion resistance, flame retardant properties and good wave transmission performance. It is mainly used in high-end aerospace, national defense, space exploration and other application fields, such as solid rocket engine casings, bulletproof armor, high-strength ropes, heat-resistant felt, etc. However, due to the disadvantage of poor composite performance with resin, its large-scale promotion and application is limited.
[0003] Graphene is one of the thinnest and strongest materials known so far, and it also has good toughness and very good thermal conductivity. It is known that based on the excellent performance of graphene materials, it has been widely introduced into the preparation process of various fibers, and the performance of composite fiber materials has been improved by modifying graphene. For example, Chinese patent CN115216857B discloses a process for preparing heterocyclic aramid by modifying graphene oxide with carboxyl groups or amino graphene with amino groups, which can improve the strength and modulus of existing heterocyclic aramid without reducing the thermal stability of heterocyclic aramid.
[0004] However, in the technical field of preparation of PBO fibers, Chinese patent CN103014901A discloses a method for preparing graphene / PBO composite fibers, which is to disperse graphene oxide prepared by a modified Hummer method into deionized water to obtain a certain concentration of graphene oxide aqueous solution, and then obtain a graphene-containing monomer complex through a series of complex preparation processes, and then introduce the graphene-containing monomer complex into the preparation process of PBO fibers to achieve the preparation of graphene / PBO composite fibers. The tensile strength of the graphene / PBO composite fibers prepared by this method can be increased to 3.8-4.2 GPa, and its tensile strength can increase with the increase of the amount of graphene added. However, the process flow of this patent is complicated, not only does it need to prepare the graphene oxide monomer complex separately, but it also needs to be pre-dispersed in the raw material monomer, and the tensile strength of the obtained composite fiber is low.
[0005] Chinese patent CN103936988A also discloses a graphene nanoribbon grafted modified PBO polymer and a preparation method thereof, wherein the method uses carboxylated graphene nanoribbons to graft modify the PBO polymer, and by grafting the graphene nanoribbons to the PBO polymer, and due to the rigid structure of the graphene nanoribbons, the axial tensile properties of the PBO polymer can be significantly improved, and the tensile strength reaches 8 to 9 GPa. This patent also has the disadvantage of a complex process, and its preparation process includes a graphene carboxylation treatment process, a PBO polymerization reaction, and then a grafting reaction of the carboxylated graphene with the PBO polymerization liquid. The reaction process is long, impurities are easily introduced, and strong acidic substances are used in many steps, and the three wastes are difficult to treat, which is not conducive to industrial scale production. Summary of the invention
[0006] The purpose of the present invention is to provide a graphene oxide / PBO composite fiber and a preparation method thereof, which can enhance the interaction between molecular chains and increase the surface polarity of the fiber without affecting the surface morphology of the fiber, thereby improving the composite performance of the PBO fiber and the resin.
[0007] The present invention is achieved through the following technical scheme: a method for preparing graphene oxide / PBO composite fibers, using terephthalic acid, 4,6-diaminoresorcinol hydrochloride, phosphorus pentoxide, polyphosphoric acid and graphene oxide as raw materials, degassing, prepolymerizing and defoaming to obtain a prepolymer material containing graphene oxide, and then post-polymerizing and spinning to obtain the graphene oxide / PBO composite fibers,
[0008] The graphene oxide is graphene with nitrogen atoms and oxygen atoms on the surface, the size of the graphene meets 100nm-6μm, 80% of the particle size is less than 560nm, and the thickness is 1-3 layers;
[0009] The performance indicators of the graphene oxide / PBO composite fiber meet the following requirements:
[0010] Tensile strength: 36.0~42.0cN / dtex;
[0011] Modulus: 1200~1600cN / dtex;
[0012] Compression strength: 500~700MPa;
[0013] Thermal stability: weight retention rate is 40% at 800°C;
[0014] Water contact angle: 20°~40°;
[0015] Surface tension: 45~70mN / m.
[0016] The added amount of the graphene oxide is 0.05-0.5% of the mass of the graphene oxide / PBO composite fiber.
[0017] The molar ratio of terephthalic acid to 4,6-diaminoresorcinol hydrochloride is 1:0.95-1.05.
[0018] The amounts of the polyphosphoric acid and phosphorus pentoxide are calculated based on the solid content of the prepolymerized material and the mass percentage of the polyphosphoric acid at the end of the prepolymerization reaction, so that the solid content of the prepolymerized material is controlled at 10-20%, and the mass percentage of the polyphosphoric acid in the material at the end of the prepolymerization reaction is 78-88%.
[0019] The degassing is carried out under a pressure of 0 to 0.1 MPa, with the temperature controlled at 50 to 150° C., for 1 to 25 hours.
[0020] During the prepolymerization and degassing, the pressure is controlled to be 0-1 MPa, the temperature is 95-180° C., and the prepolymerization and degassing time is 1-10 hours.
[0021] The intrinsic viscosity of the prepolymer material is controlled to be 8-35 dl / g.
[0022] In the present invention, in the prepolymerization stage, since the added graphene oxide content is relatively small, it has little effect on the molecular weight of PBO in the prepolymerization stage. Therefore, in the process of its prepolymerization, the reasonable control of conditions such as polymerization reaction temperature and reaction time is still the main factor in improving the polymerization molecular weight. By reasonably adjusting these process conditions, the polymer structure can be controlled to ensure the growth of the molecular chain in the subsequent polymerization reaction.
[0023] The post-polymerization is a process of feeding the pre-polymerized material into a screw extruder for post-polymerization, and then filtering and degassing to obtain the post-polymerized material. The post-polymerization temperature is controlled at 150-200° C., and the post-polymerization reaction time is 1-12 hours.
[0024] The intrinsic viscosity of the post-polymerized material is controlled to be 20-35 dl / g.
[0025] In the present invention, by increasing the temperature of the post-polymerization reaction, the reaction rate can be accelerated to make the reaction process more complete. Since the system contains graphene oxide, the intrinsic viscosity of the system is improved, the degassing time can be extended, and it is more conducive to the stability of the spinning process.
[0026] The present invention also provides a graphene oxide / PBO composite fiber prepared by the above preparation method.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0028] (1) The small-sized graphene oxide added in the present invention does not significantly affect the fiber morphology, and the added graphene oxide content is small, accounting for only 0.01-0.5% of the fiber matrix mass, so it has little impact on the production cost of PBO fiber, which is conducive to engineering production and application.
[0029] (2) The present invention selects suitable small-sized graphene, and directly achieves uniform dispersion through forced stirring and screw meshing prepared by engineering without pretreatment. The added graphene oxide increases the interaction force between the molecular chains of the PBO composite fiber, thereby improving the radial compressive strength and thermal stability of the fiber.
[0030] (3) The present invention reduces the water contact angle of the obtained graphene oxide / PBO composite fiber by adding graphene oxide, increases the surface polarity, and improves the composite performance with the resin. Therefore, the strength and modulus of the prepared dipped silk fiber are improved.
[0031] (4) The present invention can obtain the desired graphene oxide / PBO composite fiber only by adding small-sized graphene oxide. During the preparation process, the original equipment and process flow for preparing PBO fibers are not changed, which saves the transformation cost of composite fiber production and is conducive to industrial-scale production.
[0032] In summary, the present invention provides a new process for engineering the preparation of graphene oxide / PBO composite fibers. The process improves the physical properties of PBO composite fibers in terms of fiber strength, modulus, thermal stability, etc. by directly adding small-sized graphene oxide to the polymerizing monomers so that the graphene oxide is dispersed in the polymer material during the polymerization process. The process has the advantages of low preparation difficulty, low investment cost, significant performance improvement, and mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Figure 3 shows the morphology, size, flake, C / O, XPS and Raman images of graphene oxide NGO. A is the SEM and laser particle size analyzer (DLS) flake size image of NGO; B is the TEM high-resolution image of NGO, C is the AFM image of NGO; D and E are the XPS spectra of NGO; and F is the Raman image of NGO.
[0034] Figure 2 Characterization diagrams of NGO / PBO composite fibers and PBO fibers, where A is the SEM image of PBO fiber and NGO (0.1%) / PBO composite fiber; B is the SEM image of NGO (0.05%) / PBO composite fiber; C is the SEM image of NGO (0.3%) / PBO composite fiber; D is the section TEM image of NGO (0.05%) / PBO composite fiber.
[0035] Figure 3Comparison of the molecular chain forces between NGO / PBO composite fibers and PBO fibers.
[0036] Figure 4 Comparison of thermal stability between NGO / PBO composite fiber and PBO fiber.
[0037] Figure 5 Comparison of the compressive strength of NGO / PBO composite fibers and PBO fibers.
[0038] Figure 6 Comparison of water drop angle and surface polarity between NGO / PBO composite fiber and PBO fiber.
[0039] Figure 7 Comparison of the tensile strength and modulus between NGO / PBO composite fiber and PBO fiber, where A is the tensile strength and modulus of PBO fiber; B is the tensile strength and modulus of NGO / PBO composite fiber. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0041] Example 1: Graphene oxide / PBO composite fiber Ⅰ
[0042] The graphene oxide used in this embodiment is graphene (NGO) with nitrogen atoms and oxygen atoms on the surface. The size of the graphene is about 500nm and the thickness is 2 to 3 layers. Figure 1 As shown, Figure 1 A in the middle shows the SEM and laser particle size analyzer (DLS) slice size images of NGO, which shows that most of the NGO is around 500nm in size; Figure 1 The middle B shows a high-resolution TEM image of NGO, which shows that the NGO layer is relatively thin; Figure 1 The AFM image of NGO is shown in C. In the image, it can be seen that the NGO layer is about 1.4nm, indicating that the graphene oxide layer is 2 to 3 layers; Figure 1 D and E in the middle show the XPS spectra of NGO, where it can be seen that the C / O ratio of graphene oxide is 3.76, with more CO single bonds; Figure 1 F in the figure shows the ID / IG=0.949 of the Raman graphene oxide of NGO, indicating that the surface of graphene oxide carries nitrogen atoms and oxygen atoms.
[0043] In a mixing kettle, 19.38 kg of polyphosphoric acid, 0.25 kg of phosphorus pentoxide, 1.66 kg of terephthalic acid, 1.76 kg of 4,6-diaminoresorcinol hydrochloride and 0.01 kg of graphene oxide were sequentially added, the kettle was evacuated, the pressure in the kettle was controlled to be 0 MPa, the temperature was controlled to be 55°C, and degassing was performed for 15 hours. Then, the pressure in the kettle was adjusted to 0.5 MPa, the temperature was adjusted to 120°C, and prepolymerization and degassing were performed for 8 hours to obtain a prepolymerized material with a solid content of 15%, and the intrinsic viscosity of the prepolymerized material was 16 dL / g.
[0044] The prepolymerized material was sent into a screw extruder for post-polymerization. The post-polymerization temperature was controlled to be 200°C and the post-polymerization reaction time was 10 hours. During the post-polymerization, the intrinsic viscosity of the post-polymerized material was controlled to be 25 dL / g. The post-polymerized material was further degassed and spun to obtain graphene oxide / PBO composite fiber I.
[0045] Example 2: Graphene oxide / PBO composite fiber II
[0046] In a mixing kettle, 25.43 kg of polyphosphoric acid, 0.40 kg of phosphorus pentoxide, 1.8 kg of terephthalic acid, 2.0 kg of 4,6-diaminoresorcinol hydrochloride and 0.03 kg of graphene oxide (same as in Example 1) were sequentially added, the kettle was evacuated, the pressure in the kettle was controlled to be 0.1 MPa, the temperature was 150°C, and degassing was performed for 1 hour. Then, the pressure in the kettle was adjusted to 1 MPa and the temperature was adjusted to 95°C, and prepolymerization and degassing were performed for 10 hours to obtain a prepolymerized material with a solid content of 13%, and the intrinsic viscosity of the prepolymerized material was 18 dL / g.
[0047] The prepolymerized material was sent into a screw extruder for post-polymerization. The post-polymerization temperature was controlled to be 150°C and the post-polymerization reaction time was 12h. During the post-polymerization, the intrinsic viscosity of the post-polymerized material was controlled to be 29dL / g. The post-polymerized material was further degassed and spun to obtain graphene oxide / PBO composite fiber II.
[0048] Example 3: Graphene oxide / PBO composite fiber III
[0049] In a mixing kettle, 15.28 kg of polyphosphoric acid, 0.20 kg of phosphorus pentoxide, 1.5 kg of terephthalic acid, 1.63 kg of 4,6-diaminoresorcinol hydrochloride and 0.06 kg of graphene oxide (same as in Example 1) were sequentially added, the kettle was evacuated, the pressure in the kettle was controlled to be 0.05 MPa, the temperature was 50°C, and degassing was performed for 25 hours. Then, the pressure in the kettle was adjusted to 0.2 MPa, the temperature was adjusted to 120°C, and prepolymerization and degassing were performed for 5 hours to obtain a prepolymerized material with a solid content of 17%, and the intrinsic viscosity of the prepolymerized material was 21 dl / g.
[0050] The prepolymerized material is sent into a screw extruder for post-polymerization. The post-polymerization temperature is controlled to be 180°C, and the post-polymerization reaction time is 4 hours. During the post-polymerization, the intrinsic viscosity of the post-polymerized material is controlled to be 35 dl / g. The post-polymerized material is further degassed and spun to obtain graphene oxide / PBO composite fiber III.
[0051] Example 4: Graphene oxide / PBO composite fiber IV
[0052] In a mixing kettle, 28.0 kg of polyphosphoric acid, 0.30 kg of phosphorus pentoxide, 1.70 kg of terephthalic acid, 1.76 kg of 4,6-diaminoresorcinol hydrochloride and 0.16 kg of graphene oxide (same as in Example 1) were sequentially added, the kettle was evacuated, the pressure in the kettle was controlled to be 0.1 MPa, the temperature was 85°C, and degassing was performed for 12 hours. Then, the pressure in the kettle was adjusted to 0.8 MPa, the temperature was adjusted to 150°C, and prepolymerization and degassing were performed for 8 hours to obtain a prepolymerized material with a solid content of 11%, and the intrinsic viscosity of the prepolymerized material was 13 dl / g.
[0053] The prepolymerized material was sent to a screw extruder for post-polymerization. The post-polymerization temperature was controlled to be 175°C and the post-polymerization reaction time was 9 hours. During the post-polymerization, the intrinsic viscosity of the post-polymerized material was controlled to be 23 dl / g. The post-polymerized material was further degassed and spun to obtain graphene oxide / PBO composite fiber IV.
[0054] Comparative Example 1: PBO fiber
[0055] This comparative example relates to the preparation process of PBO fiber, which differs from Example 1 in that graphene oxide is not added, and the rest of the preparation process and related process parameters are the same. At the same time, the control process of the post-polymerization stage is slightly adjusted.
[0056] During the post-polymerization, the post-polymerization temperature is controlled to be 175° C., the post-polymerization reaction time is 9 hours, and the characteristic viscosity of the post-polymerized material is controlled to be 20 dl / g. The post-polymerized material is further degassed and spun to obtain PBO fibers.
[0057] Comparative Example 2: Graphene / PBO composite fiber
[0058] This comparative example involves a preparation process of graphene / PBO composite fibers, which differs from Example 1 only in that different graphene oxide is used, and the rest of the preparation process flow and related process parameters are the same.
[0059] In this comparative example, graphene oxide uses graphene with carboxyl groups on the surface, the size of the graphene satisfies 100 nm to 3 μm, and the thickness is 1 to 3 layers (see patent CN115216857B).
[0060] The performance of the graphene oxide / PBO composite fibers of Examples 1 to 4, the PBO fibers of Comparative Document 1, and the graphene / PBO composite fibers of Comparative Example 2 were tested, wherein the tensile strength and modulus were tested according to the method of ASTM-D885; the compressive strength was tested according to the method of ASTM D3410; the thermal stability was tested according to the thermogravimetric analysis method of ASTM E1131; and the water contact angle and surface polarity were tested according to the contact angle measurement method of ASTM D7334-08.
[0061] The test results of the above embodiments and comparative examples are shown in Table 1.
[0062] Table 1
[0063]
[0064] As can be seen from Table 1 above, the present invention can effectively improve the overall performance of the PBO composite fiber, especially in terms of fiber strength, modulus, compressive strength, thermal stability, etc., by adding graphene with nitrogen atoms and oxygen atoms on the surface of suitable size, and directly using stirring and screw meshing to achieve uniform dispersion during the preparation process. The preparation process is simple, has little impact on the production cost of PBO fiber, and has great prospects for industrial production.
[0065] The present invention further compares the relevant properties of the NGO / PBO composite fiber and the PBO fiber, wherein the preparation process of the NGO / PBO composite fiber used refers to Example 1, the NGO addition amounts are 0.05%, 0.1% and 0.3% respectively based on the mass of the graphene oxide / PBO composite fiber, and the preparation process of the PBO fiber refers to Comparative Example 1.
[0066] (1) Composite fiber characterization
[0067] The NGO / PBO composite fibers and PBO fibers were analyzed by SEM scanning electron microscope. Figure 2 shown. Figure 2 A, B, and C are SEM images of PBO fiber and NGO / PBO composite fiber with NGO added at 0.1%, 0.05%, and 0.3%, respectively. Compared with PBO fiber, the morphology of NGO / PBO composite fiber has not changed significantly, indicating that the addition of NGO has no significant effect on the whole system. Figure 2 Figure D is a TEM image of a section of NGO / PBO fiber with an NGO addition of 0.1%. It can be seen from the figure that NGO is evenly dispersed in the PBO fiber, and the size of NGO in the composite fiber is consistent with that of the raw material NGO.
[0068] (2) Stress relaxation test
[0069] The NGO / PBO composite fiber and PBO fiber were strained under a certain stress, and the stress was released through the slip between molecular chains. The stress retention rate showed that the anti-slip property between molecular chains of the NGO / PBO composite fiber with 0.1% NGO addition was improved compared with that of the PBO fiber without NGO addition. Figure 3 shown.
[0070] (3) Thermogravimetric experiment
[0071] Thermogravimetric experiments on NGO / PBO composite fibers and PBO fibers can be used to obtain the weight retention rate of the material as the temperature changes. Figure 4 As shown in the figure, the thermal stability of NGO / PBO composite fibers with NGO addition of 0.1% is improved compared with PBO fibers without NGO addition.
[0072] (4) Compression strength
[0073] The NGO / PBO composite fiber and PBO fiber were tested for compressive strength. Figure 5 As shown, the test results show that the addition of 0.1% NGO enhances the interaction between the molecular chains of the PBO fiber, so that the radial compressive strength of the NGO / PBO composite fiber is significantly improved compared with the PBO fiber without the addition of NGO.
[0074] (5) Water drop angle
[0075] The water contact angles of NGO / PBO composite fibers and PBO fibers were measured using a water drop angle meter. The surface polarity of the fibers was characterized to show that the water contact angle of the fibers decreased and the surface energy increased after the addition of graphene oxide, indicating that the surface polarity of the fibers increased. For details, see Figure 6 shown.
[0076] (6) Mechanical properties test
[0077] The NGO / PBO composite fiber and PBO fiber were prepared into dipped yarn and then the mechanical properties were tested. From the tensile strength and modulus data, it can be seen that the tensile strength and modulus of the NGO / PBO composite fiber with an NGO addition of 0.1% increased. This is due to the increase in fiber mechanical strength, surface polarity and resin adhesion. For details, see Figure 7 shown.
[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for industrially preparing graphene oxide / PBO composite fibers, characterized in that: In a mixing kettle, terephthalic acid, 4,6-diaminoresorcinol hydrochloride, phosphorus pentoxide, polyphosphoric acid and graphene oxide are sequentially added, and a prepolymerized material containing graphene oxide is obtained through degassing, prepolymerization and defoaming, and then a graphene oxide / PBO composite fiber is obtained through post-polymerization and spinning. The graphene oxide is graphene with nitrogen atoms and oxygen atoms on the surface, the size of the graphene is 100nm-6μm, 80% of the particle size is less than 560nm, and the thickness is 1-3 layers. The amount of graphene oxide added is 0.05-0.5% of the mass of the graphene oxide / PBO composite fiber. The performance indicators of the graphene oxide / PBO composite fiber meet the following requirements: Tensile strength: 36.0~42.0cN / dtex; Modulus: 1200~1600cN / dtex; Compression strength: 500~700MPa; Thermal stability: weight retention rate is 40% at 800°C; Water contact angle: 20°~40°; Surface tension: 45~70mN / m.
2. The method according to claim 1, characterized in that: The molar ratio of terephthalic acid to 4,6-diaminoresorcinol hydrochloride is 1:0.95-1.
05.
3. The method according to claim 1, characterized in that: The amounts of the polyphosphoric acid and phosphorus pentoxide are calculated based on the solid content of the prepolymerized material and the mass percentage of phosphorus pentoxide at the end of the prepolymerization reaction, so that the solid content of the prepolymerized material is controlled at 10-20%, and the mass percentage of phosphorus pentoxide in the material at the end of the prepolymerization reaction is 80-90%.
4. The method according to claim 1, characterized in that: The degassing is carried out under a pressure of 0 to 0.1 MPa, with the temperature controlled at 50 to 150° C., for 1 to 25 hours.
5. The method according to claim 1, characterized in that: During the prepolymerization and degassing, the pressure is controlled to be 0-1 MPa, the temperature is 95-180° C., and the prepolymerization and degassing time is 1-10 hours.
6. The method according to claim 1, characterized in that: The intrinsic viscosity of the prepolymer material is controlled to be 8-35 dl / g.
7. The method according to claim 1, characterized in that: The post-polymerization is a process in which the pre-polymerized material is fed into a screw extruder for post-polymerization, and then filtered and degassed to obtain the post-polymerized material.
8. The method according to claim 7, characterized in that: The intrinsic viscosity of the post-polymerized material is controlled to be 20-35 dl / g.
9. A graphene oxide / PBO composite fiber obtained by the method according to any one of claims 1 to 8.
